Алмазный поликристаллический композиционный материал для оснащения бурового инструмента - Шульженко, А.А.; Богданов, Р.К.; Гаргин, В.Г.; Русинова, Н.А.; Ткач, В.Н.; Закора, А.П.; Александрова, Л.И.; Исонкин, А.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The structure, strength, hardness and wear resistance of composite materials received under high pressure andhigh temperature in Cdiam+Co+WC and Cdiam+Co+Ni+WC in Nb-screen were considered. The most highest mechanical characteristics were obtained under sintering of the composite additionally containing Ni.